Increasing the role of women's farmer groups in Tempursari Village, Candimulyo, Magelang, through a culinary business based on banana and taro processing - Retno Rusdjijati; Alfian Syarifuddin; Oesman Raliby Al Manan; Agus Suprapto (Universitas Muhammadiyah Magelang, 2021)
Banana and taro are two of the many plants that grow in Tempursari Village. These commodities will have a low selling value if traded directly. As a result, a processed food diversification strategy is required to increase the economic value of these plants, such as processed chips with flavor variants based on the intended target market. The mentoring activity was carried out with the participation of 20 participants, who were representatives from two hamlets. Outreach activities, training, practice, and mentoring are all part of the implementation process. Based on these activities, the outcomes of processed food products, particularly banana chips and taro chips, have the potential to provide an alternative method of increasing the economy by utilizing abundant natural resources.